Implementation of Arts Education in Society Through The Thematic Community Service Program (Harmonia: Journal of Arts Research and Education, 2018)
Since the transmission of arts education in the family is limited in Indonesia, the exploration of teaching strategy for community becomes imperative as a form of informal education. This article aims to report research results on the implementation of arts education in society through thematic community service program, namely Pos Pemberdayaan Keluarga (POSDAYA) or â€œfamily empowerment post.â€ This qualitative study used a project-based research method, which began by diagnosing the problems, creating a plan for activities, implementing the plan, and evaluating the results. Participants of this research were women and children from Bandung Barat Regency of West Java and students of Universitas Pendidikan Indonesia. Data were collected from interviews, participant observation, and study documentation. The data were triangulated and interpreted. The research found a collaborative teaching strategy between students, advisors, and women who worked for POSDAYA to implement arts education for children through creating dances and musical dramas. The story in the drama contains moral values such as caring for others, appreciating oneâ€™s parents, tolerance, and environmental awareness. Implementation of arts education through the community service program conducted by students and or faculty members is beneficial to develop childrenâ€™s creativity and character.